Relaxation techniques using Quranic recitation (murotal) can reduce blood pressure in hypertensive patients - Barus, Sadaukur Br; aminah, Siti (Adult Health Nursing Journal, 2024)
Introduction:  Hypertension is a major global health concern, significantly increasing the risk of cardiovascular diseases. Various non-pharmacological interventions, such as relaxation techniques, have been explored to manage hypertension effectively. Listening to Quranic verses has been suggested as a relaxation method that may contribute to lowering blood pressure. However, empirical studies examining its effectiveness remain limited. Objectives:  This study aims to investigate the effect of listening to Quranic recitation as a relaxation technique on reducing blood pressure among hypertensive patients at Prajekan Public Health Center. Methods:  A quasi-experimental study with a pretest-posttest control group design was conducted. A total of 60 hypertensive patients were selected using purposive sampling and divided equally into an intervention group (listening to Quranic recitation) and a control group (standard treatment without relaxation intervention). Blood pressure measurements were taken before and after the intervention. Data were analyzed using Wilcoxon signed-rank test . Results:  The findings showed a significant reduction in systolic and diastolic blood pressure in the intervention group compared to the control group (p < 0.05). The mean reduction in systolic blood pressure was 10 mmHg, and the diastolic blood pressure reduced by an average of 7 mmHg. This suggests that listening to Quranic recitation has a beneficial effect on blood pressure reduction. Conclusions:  Listening to Quranic recitation as a relaxation technique can be an effective complementary therapy for managing hypertension. Further research with larger sample sizes and different populations is recommended to confirm these findings